Experiences of Left-Handed Undergraduates in a Dental Faculty in Malaysia - Wan Mohamad Nasir Wan Othman; Azlan Jaafar; Rahimah Abd Wahab; Khairunnisa’ Harun; Aws Hashim Ali (Univ Sains Malaysia, SCH Dental Sciences, 2024)
Indexed by WOS/ Scopus